Patient satisfaction towards dental services in the Faculty of Dentistry, Universiti Teknologi MARA (UiTM), Malaysia / N.M.M.N.M. Rosdy, A.A. Kassim and M.I. Maruan - N. M. M., N. M. Rosdy; A. A., Kassim; M. I., Maruan (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Objectives: This study aimed to determine patients' satisfaction in the quality of dental care provided by the Faculty of Dentistry, UiTM and to identify specific aspects in the service for improvement. Methods: A crosssectional study was conducted between June and December 2018 in the faculty's clinics using a validated bilingual Short-Form Patient Satisfaction Questionnaire (PSQ-18) scale. Results: A total of 384 subjects comprised of 57.9% females and 41.8% males were recruited for this study. 92.2% of the respondent were Malay. Most of the subjects had at least two visits (43.4%) in the past. There were seven subscales studied based on the questionnaires: General Satisfaction; Technical Quality; Interpersonal Manner; Communication; Financial Aspects; Time Spent with Doctor; Accessibility and Convenience. There were 51% of the respondents who were very satisfied with the service provided in general. More specifically, 60.8% and 55.8% of respondents were very satisfied with the technical quality and interpersonal manner of the clinician, respectively. Other subscales of the questionnaires were on the communication between clinicians and patients whereby 56.6% were very satisfied. Remarkably, only 50.8% of respondents were satisfied with the financial aspects, even though the majority of patients were paying at no cost when treated by students. In terms of time spent with doctor and accessibility to the clinician, 54.0% and 55.5% of respondents were satisfied, respectively. Conclusion: Generally, patients were satisfied with the dental services provided in the Faculty of Dentistry Universiti Teknologi MARA (UiTM). However, some aspects of service can be further improved.